Impact of Deep Margin Elevation Procedures Upon Periodontal Parameters: A Systematic Review - Chun, Eliseo Pablo; de Andrade, Guilherme S.; Grassi, Elisa D. A. [UNESP]; Garaicoa, Jorge; Garaicoa-Pazmino, Carlos (My University, 2023)
Introduction: Deep margin elevation (DME) is an emerging technique attempting to minimize the need for surgical procedures (i.e., crown lengthening [CL]), deliver indirect restorations in one clinical session and reduce overall treatment time. The present study evaluated the impact of DME upon periodontal measurements based exclusively on human studies. Methods: A literature search was performed by two independent reviewers in several databases including PubMed, EMBASE, and Cochrane Central up to March 2022. This review searched for randomized human trials, cohort (prospective/ retrospective) and/or case series studies using DME, reporting periodontal (i.e. marginal bone levels [MBL], probing depths [PD], bleeding on probing [BoP], recession [REC], clinical attachment level [CAL]), and the type of approach (non-surgical or surgical) with at least >3 months of post-operative outcomes. Results: None of the included studies reported MBL, REC or CAL, and thus, results were limited to PD and BoP. BoP was increased when the distance between restorative margin and alveolar bone was approximately <2mm. Non-surgical and surgical DME approaches led to different outcomes in PD (0.26±0.77mm vs-0.39±0.85mm) and BoP (31.50% vs-22.33%). Conclusions: Limited findings of the present systematic review can be drawn and thus, the impact of DME upon the periodontium remains inconclusive.
Keywords: Composite Resins; Crown Lengthening; Deep Margin Elevation; Gingivectomy; Inflammation